Effect of the chemical composition of fluid foods on the rate of fouling processing during sterilization - Budianto, Budianto; Feri, Zefky Okta; Suparmi, Anik; Arifin, Muh Jaenal (Vitae, 2023)
Background: This research was motivated by the determination of the sanitation schedule in the heat exchanger area for some products (milk, avocado juice, and orange juice), as well as the inconsistency of the results of previous studies related to the chemical composition of the fouling layer. Objectives: a) to test the effect of raw material composition on the chemical composition of the fouling layer. b) to test microbial growth's effect on fouling's chemical composition (protein). Methods: mathematical derivation of the formation process of Resistant Dirt Factor (Rd) in the form of an Equation; ANOVA was used to test the effect of the dependent variable (protein) and predictor (microbial). Results: a) The composition of the raw material strongly influences the chemical composition of the fouling layer; b) There is a strong effect between microbial growth and protein content as a fouling composition (p<0.05). Conclusion: A strong influence between microbial growth and the composition of the fouling layer (protein) can close the research gap related to the inconsistency of previous research results (fouling layer composition), so there is no prolonged debate.